Life style characteristics of hospital paramedical healthcare professionals: a study from a tertiary care hospital, Pondicherry - Ramya, Neelakandan; Shankar, Sethu Prabhu (International Journal of Research in Medical Sciences, 2017)
Background: Life style is linked with future cardiovascular diseases. The aim of the work was to study the life style characteristics of hospital paramedical healthcare professionals. Methods: Paramedical professionals working in Aaruapadai veedu medical college and hospital were taken up for the study. The study was done as a cross sectional study using a pretested questionnaire method. Age, height, weight, waist circumference, diet pattern, physical activity, sleep and yoga pattern in all the hospital paramedical professionals were collected and studied. Results: Of the total one hundred hospital paramedical professionals, there were 90 female paramedical professionals. Among the female paramedical professionals, there were 69 of age less than 30years. Normal body mass index of less than 25 was seen (56) 62% of female paramedical professionals. Nine paramedical professionals had abdominal obesity. Of the total 10 male paramedical professionals 6 (60%) were taking food at improper time. Seven male and 58 female paramedical professionals did not do any form of exercise. A total of 84 female paramedical professionals were taking carbohydrate rich diet. Nineteen female paramedical professionals were doing regular exercise and three paramedical professionals were doing yoga. Eighty-five female paramedical professionals had refreshing normal sleep. Conclusions: Hospital paramedical healthcare professionals had a poor physical activity and diet pattern. The prevalence of abdominal obesity was less in paramedical professionals.